Propagating fruit crops through air-layering - Kishore, Kundan; Singh, H S (Indian Horticulture, 2015)
Under eastern tropical hot and humid climatic conditions the best duration for air-layering in elephant apple (Dillenia indica) and star gooseberry (Phyllanthus acidus) was between 16 July and 16 August, whereas 1 July to 1 August was optimized duration for air-layering in rose apple (Syzygium jambos) and watery rose apple (Syzygium aqueum).